Controllable Synthesis of Zn2GeO4 Nanorods for Photocatalytic Reduction of Aqueous Cr(VI) and Oxidation of Organic Pollutants - Jin Liu; Xiaodan Jin; Yurong Shi; Mingming Qiao (Journal of Nanotechnology)
Zn2GeO4 nanorods were successfully synthesized by a simple hydrothermal method. The composition, morphology, and optical properties of as-synthesized Zn2GeO4 samples were characterized by X-ray diffraction, scan electron microscopy, and UV-vis diffuse reflectance spectra. The photocatalytic properties of Zn2GeO4 nanorods were evaluated by the reduction of Cr(VI) and oxidation of organic pollutants in aqueous solution. The effects of solution pH on Cr(VI) reduction by Zn2GeO4 nanorods were studied in detail. The results indicated that the efficiency of Cr(VI) reduction was highest at pH 5.96. Moreover, Zn2GeO4 nanorods also showed excellent photocatalytic ability for the oxidation of organic pollutants such as rhodamine B and 4-nitrophenol.